Biocontrol of Rhizoctonia Solani in Cucumber Plants Using Endobacteria: Effects On Disease Severity and Chlorophyll Content - Khaldoon Faris Saeed; Abdullah Mahmood Othman (Nabatia, 2023)
This study aimed to investigate the potential of endobacteria isolated from different parts of cucumber plants (roots, stems, and leaves) to inhibit the growth of the pathogenic fungus Rhizoctonia solani. Molecular identification confirmed the presence of R. solani in cucumber plants displaying symptoms of wilting and yellowing. Laboratory experiments revealed variations in citrate consumption and gram stain results among different endobacterial isolates. In field experiments, treatments involving Bacillus subtilis with Tricozone and Pseudomonas fluorescens with Tricozone demonstrated significant reductions in disease severity and increased chlorophyll content in cucumber plants compared to the pathogen control. Additionally, Acinetobacter baumannii with Hymazole at the first concentration showed superior effects on leaf area. These findings highlight the potential of endobacteria as biocontrol agents against R. solani, with implications for improving cucumber plant health and productivity.